Exploring Women’s Housing Challenges: Legal and Policy Solutions for Women’s Access to Adequate Housing - Sohaimi, Nor Suzylah; Ismail, Nur Syakiran Akmal; Mega Nisfa Makhroja; Norhanizan Sahib; Ahmad Zuhairi (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
Women face significant challenges in accessing affordable and adequate housing, particularly in developing countries where discriminatory practices, gender inequality, and restrictive legal frameworks persist. Despite housing being recognised as a fundamental human right by international laws, many women around the world continue to face insecurity in this area. This issue remains largely underexplored, even though it directly impacts women’s economic and social well-being, safety, and overall quality of life. This study seeks to explore the patterns of research on women’s housing issues, identify the global challenges faced by women in accessing housing, and provide suggestions for the adoption of international practices and regulations to overcome these barriers. The research was based on a systematic literature review (SLR), which critically examined global studies on women’s housing to understand the core issues and solutions proposed by various nations. Key findings indicated that women encounter major obstacles, such as housing insecurity, gender inequality in housing access, and risks related to safety, including sexual violence. International practices, such as the Housing First model, gender-sensitive urban planning, and the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), offer frameworks to mitigate these issues. Policy recommendations include the enforcement of anti-discrimination laws, expansion of affordable housing programmes, and the provision of integrated support services for women facing housing insecurity.